Current Prevention and Clinical Management of COVID-19 in India - Shanmugam, Dharani Abirama Sundari; Choudhury, Rishi; JAVN, SB; Ganesan, Vinoth Kumar; Malngiang, Magrita; Sakthivel, Meenakumari; Kar, Abhijit; Franco, Abishek; Kumar, Merugumolu Vijay (Iraqi Journal of Science, 2024)
The COVID-19 pandemic has clasped the world by furore storm. India has been the epicenter of the surge in COVID cases since March 2021 which is being considered as the second wave. With every passing week, new guidelines were being implemented by various states as well as the central government to control the situation. Hospitals were running out of beds, oxygen, and medicinal supply with patients with comorbidities suffering the most. A handful of drugs have been approved for direct or emergency use to counter the situation. However, over time some of these drugs have faced strong backlash for being ineffective and hence are no longer in use. In this review, we shall study various vaccines that have been approved in India and abroad and, also various drugs which were approved for treating the COVID-19 patients.